The effect of waste wash water on concrete properties. Sabriani - Eh Chan, Sakila Sabriani (2010)
Recycling is the act of processing the used material to create new product. The usage of tap water is getting more intense with the advanced development in manufactory industry included in concrete ready mix plant. In order to reduce the tap water consumption, waste wash water can be used as substitute in concrete mixture. Normally, in concrete ready-mixed plant they using 700 to 1300 liters of tap water to wash the truck after delivery the concrete in every day. Therefore, new alternative to recycle and reuse the waste wash water is important to avoid the evironmental problem and wastage. Several researches have been developed a new way to reuse this water in concrete and it was found that the use waste wash water in the concrete mix is a possible. It was shown certain properties of concrete have been improved and there is no adverse effect to the concrete quality. In this study, wash water is used as a replacement of tap water in order to study the concrete compressive strength and it micro properties.Tests conducted by 100% replacing the tap water with waste wash water in concrete mixture. It was shown, the using of waste wash water has improved performance of concrete in terms of concrete strength, water absorption and porosity.